Residual currents and fluxes through the mouth of Vassova coastal lagoon - SYLAIOS, G.; TSIHRINTZIS, V.A.; AKRATOS, CH.; TSIKLIRAS, A.; HARALAMBIDOU, K. (Mediterranean Marine Science, 2003)
An intensive sampling program of physical and chemical parameters at the mouth of Vassova lagoon (Northern Greece) during 4 separate tidal cycles is described. The study aims at understanding the tidal circulation and estimating the instantaneous and residual fluxes of water, salt and nutrients through the entrance canal of this micro-tidal lagoon. Results showed that tidal flood exceeded in duration tidal ebb, under spring and neap tidal conditions. Ebb tidal currents were recorded higher than flood currents, especially under neap tidal conditions. Unsteady flow characterized the temporal variation of longitudinal and lateral velocity, inducing a rightward deflection on flood or ebb flow. The intra-tidal variability of dissolved inorganic nitrogen showed seasonal dependence, with higher values during September, October and early March, and lower during the late March period. Residual current and flux analysis into a Eulerian and a mass transport Stokes drift mechanism illustrated that advective water and dissolved parameters (i.e., salt and nitrates, phosphates and chlorophyll-·) fluxes were an order of magnitude higher than tidal pumping effects. Water and dissolved constituents moved into the lagoon under neap tidal conditions and out of the lagoon during spring tidal conditions. Calculated flushing times ranged from 5 to 14 days, with neap tidal conditions and nearly zero freshwater discharge producing the longer flushing time. Lower water flushing effects were generated under spring tides and increased precipitation.